De l’avantage (ou non) de définir la science-fiction (comme expérience de pensée) - Bastien Descombes (ReS Futurae, 2022)
This article proposes a first approach of the science-fiction genre through the lens of thought experiment. Thought experiment opens a path to a new definition of the genre that would enable to avoid the main pitfalls raised by John Rieder. Therefore it provides an opportunity to take simultaneously into account the historical context of the generic objects, their reception and their use. A first definition of thought experiment will enable us to define the fictional nature and will as well raise some functional features relating to this kind of experiment. Then we will try to integrate the thought experiment as the characteristic feature of the promise of SF genre, as defined by François Jost. Finally, we will draft an analysis of several objects founded on five proposals and confirmed by a semantic / syntactic approach, inspired by Rick Altman’s works.